(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Women’s entrepreneurship is important for women’s position in society,and for economic development of a country. Many scholars pointed out that womenfaces diverse challenges in doing business in a patriarchal. Women are nowinvolved in economic activities than in the past, women constitute around 10percent of the country’s total business entrepreneurs. The present study is aneffort to find out the factors which act as pull and push factors to engagewomen in entrepreneurship development in India. In this study mixed methodapproach has been chosen. To attain the objective of the research researchersrelied solely on the secondary sources. The study revealed that Governmentagencies provide policy, legal and financial support with active support fromnon-State actors. On the contrary, they do not get proper support from allrelevant institutions because of corruption and lack of information. It issuggested that combined initiatives of Government and nongovernmentinstitutions will be successful in meeting the needs of business women inIndia. Entrepreneurship among womenhas been a matter of recent concern in the country. The hidden entrepreneurialpotential of women has gradually been changing with the sensitivity to theirrole and economic status in the society. Women are increasingly being consciousof their existence, their rights, and work situation. However, New Industrialpolicy of 2009-14 and other schemes which are started post and recent arehelping to the poor women and women entrepreneurs in the form of generation ofemployment, income and to improve their social status. Definitely, thesocio-economic conditions of women entrepreneurs would improve, if theseschemes, programmes and policies are implemented strictly both by the Centreand the State governments and it goes a long way for the growth and developmentof women, women entrepreneurs and the industrial sector of the Indian economy.